Global longitudinal strain as a predictor of cardiovascular events and mortality in patients with ischemic heart disease and heart failure with preserved/mid-range ejection fraction. (14th October 2021) - Santos, J; Pires, I; Neto, V; Goncalves, L; Correia, J; Almeida, I; Correia, E
Abstract: Introduction: Global longitudinal strain (GLS) is considered a more sensitive marker of systolic dysfunction than other measures commonly used in clinical practice, such as left ventricle ejection fraction (EF). Our objective was to evaluate the impact of reduced GLS in death and cardiovascular events in patients hospitalized due to heart failure with mid-range or preserved ejection fraction, with previous history of acute myocardial infarction. Methods: A retrospective analysis of 170 patients admitted to a Cardiology ward due to acute heart failure (AHF) was performed. Patients with reduced EF (Simpson biplane method - EF<40%) were excluded based on echocardiographic evaluation after AHF stabilization. GLS measured by "speckle tracking" technique was calculated for each patient. Measurements were made by the same operator to minimize interoperator variability. Mann-Whitney U test was used for univariate analysis. Kaplan-Meier survival plots and Cox-regression analysis were performed to assess differences in 12-month mortality (12MM) and in the composite endpoint of cardiovascular event or death (12CVM) at 12 months. Results: A total of 127 patients were included. Mean patient age was 64 (±14) years; 72% were men. 48% of patients had history of ST elevation AMI. Mean EF was 54% (±8) and mean GLS was −14.3 (±3.8). Rates of 12MM and 12CV M were 14.2% and 19.3%, respectively. A statistically significant association between 12MM and 12MCV was found in univariate analysis for GLS (p<0.001). Kaplan-Meyer survival plots revealed that a compromised GLS (<−16) was associated with significantly increased 12MM (23% vs 2.5%, X 2 : 7.999, p=0.005) and 12CVM (26.6% vs 10%, X 2 : 4.139, p=0.042). When stratified by mid-range vs preserved EF, GLS <−16 was associated with worse outcomes, although the results did not reach statistical significance (p>0.05). However, when considering a severely compromised GLS (<−13), GLS was significantly associated with increased 12MM (52% vs 8.3%, X 2 : 5.533, p=0.019) and 12CVM (50% vs 8.3%, X2: 4.970, p=0.026), in the subgroup of patients with heart failure with mid-range EF. Cox-regression analysis demonstrated that GLS was independently associated with 12MM (HR: 0.668p, <0.001) and the 12CVM composite endpoint (HR: 0.819, p=0.008), even after adjustment for other important prognostic markers such as chronic kidney disease, pulmonary disease and diabetes, with significant hazard ratio reduction for each positive point increase in GLS. Conclusion: GLS is an independent predictor of 12MM and 12CVM in patients hospitalized due to AHF, with an EF ≥40% and previous history of acute myocardial infarction. In the subgroup of patients with heart failure with mid-range EF, a severely compromised GLS (<−13) is a strong predictor of 12MM and 12CVM. Funding Acknowledgement: Type of funding sources: None.